STUDY OF THE FUNCTION OF LOCAL ACTIVITIES CENTER(CASE STUDY)THE TOWN OF SOREANG, BANDUNG REGENCY AS THE CAPITAL - Permana, Heri; Prasetyo, Irwan; Zefri, Zefri (Journal of Green Science and Technology, 2019)
In the determination of the structure of the space of the city, where the City Go on the set as the center of local activities, while development in the town of Soreang is currently faced with various challenges, including the growing increase of the population, the limited infrastructure and land over the function so that the function of the city go unnoticed as the Centre of Local Activity hasn't been able to mengimbagi infrastructure services that should be available to the public.Study of the function of Local Activities Center take the case in the town of Soreang, strategy formulation to provide enhanced functionality for local Activities Center in the town of Soreang, Bandung Regency as the capitalAnalysis on the utilization of space occurs over the function of the land of paddy fields, became the land of housing, industry and infrastructure analysis, as well as other cities that have not been adequate as, road; Hospitals, higher education, Terminal, and utilities, this function meyebabkan Local Service Center does not seem to meet the needs of community service facilities in the town of Soreang, devote an increasing development strategies was obtained by the Center The local town of Soreang activities in the form of infrastructure development, land use strategy and strategy of institutional development as well as the role of the community to the development of the construction of the City Go as a function of local activities.Key Words: Local Activities Center Of The City As The Capital Of Bandung Regency, Soreang?